Safety Management System Implementation on Ship in Shipping Companies in Banjarmasin - Khotami, Wildani; Suharto, Imam; Herliani, Ema; Salim, Yeffriansjah; Courtney, Gurnari (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
This study aims to (1) to find out how the implementation of the safety management system on board ships at shipping companies in Banjarmasin 2) to know the safety management system on board this is of course related to occupational health and safety is a thought and effort to ensure the integrity and perfection of both physical or spiritual. with efforts to prevent and treat diseases or health problems caused by work and the work environment as well as general illnesses. Occupational safety is a series of efforts to create a safe and peaceful working atmosphere for employees who work in the company concerned and a condition that is safe and safe from suffering and damage or loss in the workplace, both when using tools, materials, machines in the process processing, packing techniques, storage, as well as maintaining and securing the work place and environment.